2017
DOI: 10.1016/j.jacc.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxidative Stress on the Heart and Vasculature

Abstract: Vascular disease and heart failure impart an enormous burden in terms of global morbidity and mortality. Although there are many different causes of cardiac and vascular disease, most share an important pathological mechanism: oxidative stress. In the failing heart, oxidative stress occurs in the myocardium and correlates with left ventricular dysfunction. Reactive oxygen species (ROS) negatively affect myocardial calcium handling, cause arrhythmias, and contribute to cardiac remodeling by inducing hypertrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
290
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(332 citation statements)
references
References 170 publications
6
290
0
9
Order By: Relevance
“…Oxidative stress has been linked to the onset of various cardiovascular complications, particularly in hypertension (Forstermann et al, 2017;McSweeney et al, 2016;Munzel et al, 2017). Ang II infusion induces aberrant ROS production in the aorta, resulting in dysfunction of the endothelium (Dikalov et al, 2014).…”
Section: Sch C Prevents Ang Ii-induced Aorta Oxidative Stress and Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress has been linked to the onset of various cardiovascular complications, particularly in hypertension (Forstermann et al, 2017;McSweeney et al, 2016;Munzel et al, 2017). Ang II infusion induces aberrant ROS production in the aorta, resulting in dysfunction of the endothelium (Dikalov et al, 2014).…”
Section: Sch C Prevents Ang Ii-induced Aorta Oxidative Stress and Rmentioning
confidence: 99%
“…Extensive cellular and molecular studies have identified putative mediators, which include increased oxidative stress, inflammation, mitochondrial dysfunction, and endothelial cell (EC) apoptosis (Hou et al, ; Kroller‐Schon et al, ; Vaka et al, ), that participate in the progression of endothelial dysfunction. Among these various functional events, oxidative stress seems to be upstream of the cascade (Forstermann, Xia, & Li, ; McSweeney, Warabi, & Siow, ; Munzel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a common factor across all contributing pathologies in CVD 21. Oxidative stress arises when the production of reactive oxygen species exceeds the total antioxidant capacity of the body.…”
Section: Contributing Pathologies Within the Cvd Spectrummentioning
confidence: 99%
“…Moreover, it has noted that there is possibility to change of endothelial cell immune phenotype to cardiac cell phenotype in animal model [22]. Whether similar effects trigger structure and functional abnormality in cell precursors that involve in the pathogenesis of HF is not well established, although accumulation of reactive oxygen species leading to the swelling and fragmentation of mitochondria of EPCs has now described as factor of decreased repair ability of precursors [23]. Indeed, enhancement of oxidative stress and mitochondrial dysfunction of EPCs may negatively effect of number and function of ones (mobbing, proliferation, regeneration, apoptosis, differentiation, cell-cell interaction, survival) through intracellular signaling pathways (Akt/nitric oxide, PI3K/nitric oxide), which may operate in signal-regulated kinase and the inflammatory genes expression, such as interleukin-6 and TNF-α, and synthesis of specific miRNAs (-126, -128, -130) [24,25].…”
Section: Epc Dysfunction As a Central Player In Hf Risk Developmentmentioning
confidence: 99%